An alternative, nonapoptotic form of programmed cell death - Sperandio, Sabina (The National Academy of Sciences, 2000)
The term apoptosis often has been used interchangeably with the term programmed cell death. Here we describe a form of programmed cell death that is distinct from apoptosis by the criteria of morphology, biochemistry, and response to apoptosis inhibitors. Morphologically, this alternative form of programmed cell death appears during development and in some cases of neurodegeneration. Despite its lack of response to caspase inhibitors and Bcl-x(L), we show that this form of cell death is driven by an alternative caspase-9 activity that is Apaf-1-independent. Characterization of this alternative form of programmed cell death should lead to new insight into cell death programs and their roles in development and degeneration.